Low-cost magnet and preparation method thereof
By adding Gd or Ce to the neodymium iron boron magnet and controlling the content of other elements, combined with the three-stage aging process, the problem of increasing the residual magnetism, coercivity and squareness of the magnet without adding heavy rare earths is solved, and a low-cost and high-performance magnet preparation is achieved.
Patent Information
- Application Number
- CN202411985558.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
How to improve the residual magnetism, coercivity and squareness of the sintered neodymium iron boron magnet without adding heavy rare earth elements Dy and Tb, especially at high temperatures?
By adding Gd or Ce to replace some light rare earth elements Pr and Nd, and adjusting the content of elements such as B, Cu, Ga, etc., combined with the three-stage aging process in the preparation of the alloy, the intergranular structure of the magnet is accurately regulated.
It realizes low-cost production of neodymium iron boron magnets, while improving its residual magnetism, coercivity and squareness to adapt to application needs under high temperature conditions.
Smart Images

Figure CN119763968A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of magnetic materials, and more specifically, to a low-cost magnet and a method for preparing the same. Background Art
[0002] Since its introduction, rare earth magnetic materials have been widely used in energy, transportation, machinery, medical appliances and other industries due to their excellent magnetic properties, and their products also involve many areas of the national economy. At present, the development of electric vehicles, wind power generation and other fields has been rapid, and the demand for improving the performance of permanent magnets is also gradually increasing.
[0003] As a rare earth magnetic material, NdFeB sintered magnet is one of the most important permanent magnets. Since many applications of NdFeB sintered magnets are in high temperature environments, they are required to have not only high remanence but also high coercivity. Among them, coercivity is the main parameter of permanent magnet materials. The higher the coercivity, the stronger its anti-demagnetization ability. When applied, not only is the coercivity of NdFeB sintered magnets as high as possible, but it is also required to have good temperature stability so that it can work under higher temperature conditions. Common methods to increase the coercivity of NdFeB sintered magnets include using heavy rare earth elements Dy and Tb to replace Nd to increase its coercivity. However, the reserves of heavy rare earth Dy and Tb are scarce and expensive. At the same time, the addition of heavy rare earth Dy and Tb will also reduce the remanence of the magnet. In addition, since Dy and Tb are susceptible to the impact of rare earth policies, there may be a risk of instability or large fluctuations in magnet prices.
[0004] Therefore, how to obtain rare earth permanent magnets with good consistency in remanence, coercivity and squareness while reducing the amount of heavy rare earth added is an urgent problem to be solved in this field. In addition, as market competition intensifies, how to further reduce the use of light rare earth (PrNd) without adding heavy rare earth is also imminent. Summary of the invention
[0005] In order to at least solve one or more of the technical problems mentioned above, the present application proposes solutions for improving the prior art in multiple aspects.
[0006] According to one aspect of the present application, the present application provides a neodymium iron boron magnet, wherein the neodymium iron boron magnet comprises the following components:
[0007] R: 28~33wt%
[0008] B: 0.85~0.94wt%,
[0009] Co: 0.05~0.6wt%,
[0010] Cu: 0.05~0.5wt%,
[0011] Ga: 0.3~0.6wt%,
[0012] M1: 0.05~1.1wt%,
[0013] M2: 0.1~0.5wt%,
[0014] Fe: 63.2~69wt%;
[0015] Wherein, R is a rare earth element, R includes at least PrNd, and R includes R1;
[0016] R1 is selected from one or both of Gd and Ce;
[0017] M1 is at least one element selected from Al and Sn;
[0018] M2 is at least one element selected from Zr, Ti and Nb;
[0019] The NdFeB magnet comprises main phase grains, thin layer grain boundary phases and triangular region grain boundary phases, wherein the distribution of the triangular region grain boundary phases satisfies the following conditions: the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet accounts for 6% to 8.5% of the total area of the cross section; the triangular region grain boundary phases include R6T 13 M1 phase, M is selected from one or more of Al, Cu, Ga, Ti, Sn, Zr, Nb, T is selected from one or two of Fe and Co, and R6T 13 The ratio R1 / R of the atomic percentage of R1 to the atomic percentage of R in the M1 phase is 6.0% to 9.0%.
[0020] According to one embodiment of the present application, the content of R is 29.5-33 wt %, and R does not include Dy and Tb.
[0021] According to one embodiment of the present application, the composition of the NdFeB magnet includes at least one of the following features:
[0022] a.Cu: 0.25-0.5wt%;
[0023] b.Al: 0.5-1.1wt%;
[0024] c.Ga: 0.3-0.45wt%;
[0025] d.Ti: 0.15~0.3wt%.
[0026] According to one embodiment of the present application, the content of R1 is 3 to 7 wt %.
[0027] According to one embodiment of the present application, the distribution of the triangular region grain boundary phase satisfies the following conditions: the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet accounts for 7% to 8.5% of the total area of the cross section; preferably, the triangular region grain boundary phase includes R6T 13 M1 phase, the R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.5% to 7%, preferably 6% to 7%.
[0028] According to one embodiment of the present application, the triangular region grain boundary phase of the NdFeB magnet includes at least one of the following features:
[0029] a. The triangular region grain boundary phase comprises an Fe-rich high M phase, and the ratio of the atomic percentage of R1 to the atomic percentage of R in the Fe-rich high M phase is R1 / R of 4.0% to 11.0%, preferably 4.0% to 9.0%;
[0030] b. The triangular region grain boundary phase includes R6T 13 M1 phase, and R6T 13 The ratio of the atomic percentage of R1 to the atomic percentage of R in the M1 phase is R1 / R, which is 6.0% to 8.5%;
[0031] c. The triangular region grain boundary phase includes a Cu-rich phase, and the ratio of the atomic percentage of R1 to the atomic percentage of R in the Cu-rich phase, R1 / R, is 4.0% to 6.5%, preferably 4.0% to 6.0%.
[0032] According to another aspect of the present application, the present application provides a method for preparing a neodymium iron boron magnet, which comprises:
[0033] 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process;
[0034] 2) crushing the quick-setting alloy flakes obtained in step 1) by hydrogen, adding additives and jet milling to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 3 to 5 μm;
[0035] 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.4-2.5T, to obtain a compact, or performing secondary isostatic pressing to obtain a compact;
[0036] 4) placing the compact obtained in step 3) into a sintering furnace, sintering and aging in a vacuum or inert atmosphere, and finally obtaining a NdFeB magnet;
[0037] The aging treatment process is a three-level aging process: the temperature of the first level aging is 800-950°C, and the insulation time is 0.5-4h; the temperature of the second level aging is 450-550°C, and the insulation time is 2-10h; the temperature of the third level aging is 600-700°C, and the insulation time is 2-10h.
[0038] According to one embodiment of the present application, in the step 4), the aging treatment process further includes: cooling to 150-250°C after the second stage aging, with a cooling rate of 3-8°C / min; cooling to room temperature after the third stage aging, with a cooling rate of 3-8°C / min.
[0039] According to one embodiment of the present application, in the step 1), the rapid solidification process includes melting the alloy raw material in a vacuum induction melting furnace at a melting temperature of 1400-1500°C, and casting the molten liquid onto a copper roller to obtain a 0.15-0.4 mm rapid solidification alloy sheet.
[0040] According to one embodiment of the present application, in the step 4), the sintering process parameters include: a sintering temperature of 1030 to 1120° C., and a sintering time of 4 to 12 hours, preferably 6 to 12 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] By reading the detailed description below with reference to the accompanying drawings, the above and other purposes, features and advantages of the exemplary embodiments of the present application will become easy to understand. In the accompanying drawings, several embodiments of the present application are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:
[0042] Figure 1 A scanning electron microscope photograph of a cross section of the magnet of Example 1 of the present application is shown;
[0043] Figure 2 A scanning electron microscope photograph of a cross section of a magnet of Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0045] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present application indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0046] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the present application. As used in this application specification and claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms. It should also be further understood that the term "and / or" used in this application specification and claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations.
[0047] The specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. Unless otherwise specified, the materials, reagents and equipment used in the examples of the present application are all obtained from conventional commercial channels.
[0048] In a first aspect, the present application provides a neodymium iron boron magnet, wherein the neodymium iron boron magnet comprises the following components:
[0049] R: 28~33wt%
[0050] B: 0.85~0.94wt%,
[0051] Co: 0.05~0.6wt%,
[0052] Cu: 0.05~0.5wt%,
[0053] Ga: 0.3~0.6wt%,
[0054] M1: 0.05~1.1wt%,
[0055] M2: 0.1~0.5wt%,
[0056] Fe: 63.2~69wt%;
[0057] Wherein, R is a rare earth element, R includes at least PrNd, and R includes R1;
[0058] R1 is selected from one or both of Gd and Ce;
[0059] M1 is at least one element selected from Al and Sn;
[0060] M2 is at least one element selected from Zr, Ti and Nb;
[0061] The NdFeB magnet comprises main phase grains, thin layer grain boundary phases and triangular region grain boundary phases, wherein the distribution of the triangular region grain boundary phases satisfies the following conditions: the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet accounts for 6% to 8.5% of the total area of the cross section; the triangular region grain boundary phases include R6T 13 M1 phase, M is selected from one or more of Al, Cu, Ga, Ti, Sn, Zr, Nb, T is selected from one or two of Fe and Co, and R6T 13 The ratio R1 / R of the atomic percentage of R1 to the atomic percentage of R in the M1 phase is 6.0% to 9.0%.
[0062] The technical solution of the embodiment of the present application adds Gd or Ce to replace part of the light rare earth elements Pr and Nd, and at the same time adjusts the content of elements such as B, Cu, and Ga, and combines the three-level aging process in the alloy preparation process, so that the area ratio of the grain boundary phase in the triangular region of the magnet is greatly increased, and R6T 13 The area ratio of the M1 phase is also improved to a certain extent; thus, the intergranular structure of the NdFeB magnet is precisely regulated. The prepared NdFeB magnet has the advantage of low cost on the one hand, and high remanence, coercive force and squareness on the other.
[0063] In some embodiments, the content of R is 29.5-33wt%, and R does not include Dy and Tb. Exemplarily, the content of R can be 29.5wt%, 30.0wt%, 30.5wt%, 31.0wt%, 31.5wt%, 32.0wt%, 32.5wt%, 33.0wt% or any value within the range composed of any of the above values. As described above, the present application effectively and accurately adjusts the intergranular structure of the NdFeB magnet by adding Gd or Ce and regulating the content of other elements, so that the composition of the NdFeB magnet does not need to add high-cost heavy rare earth elements Dy and Tb.
[0064] In some embodiments, the content of R1 is 3-7 wt %. For example, the content of R1 can be 3.0 wt %, 3.5 wt %, 4.0 wt %, 4.5 wt %, 5.0 wt %, 5.5 wt %, 6.0 wt %, 6.5 wt %, 7.0 wt % or any value within the range of any of the above values.
[0065] In some embodiments, the composition of the NdFeB magnet includes Cu: 0.25-0.5 wt%. For example, the content of Cu can be 0.25 wt%, 0.28 wt%, 0.30 wt%, 0.32 wt%, 0.35 wt%, 0.38 wt%, 0.40 wt%, 0.42 wt%, 0.45 wt%, 0.48 wt%, 0.50 wt%, or any value within the range of any of the above values.
[0066] In some embodiments, the composition of the NdFeB magnet includes Al: 0.5-1.1 wt%. For example, the content of Al can be 0.50 wt%, 0.55 wt%, 0.60 wt%, 0.65 wt%, 0.70 wt%, 0.75 wt%, 0.80 wt%, 0.85 wt%, 0.90 wt%, 0.95 wt%, 1.00 wt%, 1.05 wt%, 1.10 wt% or any value within the range of any of the above values.
[0067] In some embodiments, the composition of the NdFeB magnet includes Ga: 0.3-0.45 wt %. For example, the content of Ga can be 0.30 wt %, 0.32 wt %, 0.35 wt %, 0.38 wt %, 0.40 wt %, 0.42 wt %, 0.45 wt % or any value within the range formed by any of the above values.
[0068] In some embodiments, the composition of the NdFeB magnet includes Ti: 0.15-0.3 wt %. For example, the content of Ti can be 0.15 wt %, 0.18 wt %, 0.20 wt %, 0.22 wt %, 0.25 wt %, 0.28 wt %, 0.30 wt % or any value within the range of any of the above values.
[0069] In some embodiments, the distribution of the triangular region grain boundary phase satisfies the following condition: the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet accounts for 7% to 8.5% of the total area of the cross section. Exemplarily, the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet accounts for 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5% or any value within the range of any of the above values.
[0070] In some embodiments, the triangular region grain boundary phase includes R6T 13 M1 phase, the R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T13 The percentage of the area of the M1 phase to the total area of the cross section is 5.5% to 7%, preferably 6% to 7%. Exemplarily, the percentage of the area of all R6T13M1 phases in the cross section of the NdFeB magnet to the total area of the cross section can be 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0% or any value within the range of any of the above values.
[0071] In some embodiments, the triangular region grain boundary phase of the NdFeB magnet includes an Fe-rich high-M phase, and the ratio of the atomic percentage of R1 to the atomic percentage of R in the Fe-rich high-M phase is 4.0% to 11.0%, preferably 4.0% to 9.0%. Exemplarily, the ratio of R1 / R in the Fe-rich high-M phase is 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0% or any value within the range of any of the above values.
[0072] The Fe-rich high-M phase includes R, M and Fe, R refers to all rare earth elements, R includes R1, and R1 is selected from Gd and / or Ce; wherein the atomic percentage of Fe is higher than 40%, and the atomic percentage of M is higher than 6%.
[0073] The Cu-rich phase includes R and Cu, and the atomic percentage of Cu is higher than 15%.
[0074] In some embodiments, the triangular region grain boundary phase of the NdFeB magnet includes R6T 13 M1 phase, and R6T 13 The ratio of the atomic percentage of R1 to the atomic percentage of R in the M1 phase is 6.0% to 8.5%. 13 The ratio of R1 / R in the M1 phase is 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.8%, 8.0%, 8.2%, 8.5% or any value within the range consisting of any of the above values.
[0075] In some embodiments, the triangular region grain boundary phase of the NdFeB magnet includes a Cu-rich phase, and the ratio of the atomic percentage of R1 to the atomic percentage of R in the Cu-rich phase, R1 / R, is 4.0% to 6.5%, preferably 4.0% to 6.0%. Exemplarily, the ratio of R1 / R in the Cu-rich phase is 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, 5.8%, 6.0%, or any value within the range of any of the above values.
[0076] In a second aspect, the present application also provides a method for preparing a neodymium iron boron magnet, which comprises:
[0077] 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process;
[0078] 2) crushing the quick-setting alloy flakes obtained in step 1) by hydrogen, adding additives and jet milling to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 3 to 5 μm;
[0079] 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.4-2.5T, to obtain a compact, or performing secondary isostatic pressing to obtain a compact;
[0080] 4) placing the compact obtained in step 3) into a sintering furnace, sintering and aging in a vacuum or inert atmosphere, and finally obtaining a NdFeB magnet;
[0081] The aging treatment process is a three-level aging process: the temperature of the first level aging is 800-950°C, and the insulation time is 0.5-4h; the temperature of the second level aging is 450-550°C, and the insulation time is 2-10h; the temperature of the third level aging is 600-700°C, and the insulation time is 2-10h.
[0082] After adding the R1 element according to the technical solution of the embodiment of the present application, if only the content of other elements is adjusted, if the three-stage aging process is not adopted, the proportion of the R1 element in the grain boundary phase with the rare earth elements may be high, thereby failing to reduce the R1 / R in the grain boundary phase; however, after adopting the above-mentioned three-stage aging process, the proportion of Pr and Nd elements in the rare earth elements in the grain boundary phase can be effectively increased, and the proportion of the R1 element in the rare earth elements in the grain boundary phase can be reduced. The above-mentioned change in proportion is beneficial to the demagnetizing coupling effect, thereby improving the coercive force, remanence and squareness of the magnet.
[0083] In some embodiments, in step 1), the composition ratio of the raw material alloy of the predetermined configuration refers to the composition of the NdFeB magnet of the first aspect of the present application.
[0084] In some embodiments, in the three-stage aging process, the temperature of the first stage aging is 800-950°C, and the holding time is 0.5-4h. Exemplarily, the temperature of the first stage aging is 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, or any value within the range of any of the above values. Exemplarily, the holding time of the first stage aging is 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, or any value within the range of any of the above values.
[0085] In some embodiments, in the three-stage aging process, the temperature of the second stage aging is 450-550°C, and the holding time is 2-10 hours. Exemplarily, the temperature of the second stage aging is 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, or any value within the range of any of the above values. Exemplarily, the holding time of the second stage aging is 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any of the above values.
[0086] In some embodiments, in the three-stage aging process, the temperature of the third stage aging is 600-700°C, and the holding time is 2-10h. Exemplarily, the temperature of the third stage aging is 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, or any value within the range of any of the above values. Exemplarily, the holding time of the third stage aging is 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any of the above values.
[0087] In some embodiments, in the step 4), the aging treatment process further includes: cooling to 150-250°C after the second stage aging, with a cooling rate of 3-8°C / min; cooling to room temperature after the third stage aging, with a cooling rate of 3-8°C / min. Exemplarily, the cooling rate after the second stage aging can be 3.0°C / min, 3.5°C / min, 4.0°C / min, 4.5°C / min, 5.0°C / min, 5.5°C / min, 6.0°C / min, 6.5°C / min, 7.0°C / min, 7.5°C / min, 8.0°C / min or any value within the range of any of the above values. Illustratively, the cooling rate after the third stage aging can be 3.0°C / min, 3.5°C / min, 4.0°C / min, 4.5°C / min, 5.0°C / min, 5.5°C / min, 6.0°C / min, 6.5°C / min, 7.0°C / min, 7.5°C / min, 8.0°C / min or any value within the range composed of any of the above values.
[0088] In some embodiments, in step 1), the rapid solidification process includes melting the alloy raw material in a vacuum induction melting furnace at a melting temperature of 1400-1500°C, and casting the molten liquid onto a copper roller to obtain a 0.15-0.4 mm rapid solidification alloy sheet. Exemplarily, the melting temperature may be 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, 1460°C, 1470°C, 1480°C, 1490°C, 1500°C, or any value within the range of any of the above values.
[0089] In some embodiments, in the step 4), the process parameters of the sintering include: a sintering temperature of 1030-1120°C, a sintering time of 4-12h, preferably 6-12h. Exemplarily, the sintering temperature is 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C or any value within the range of any of the above values. Exemplarily, the sintering time is 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value within the range of any of the above values. Specific embodiments
[0091] Example 1
[0092] Magnet formula:
[0093]
[0094] 1) The alloy raw materials prepared according to the above formula are cast into quick-setting alloy sheets by a quick-setting process: the alloy raw materials are melted in a vacuum induction melting furnace at a melting temperature of 1500° C., and the molten liquid is cast onto a copper roller to obtain a 0.25 mm quick-setting alloy sheet.
[0095] 2) The quick-solidifying alloy flakes are subjected to hydrogen crushing and micro-grinding to obtain raw alloy powder; wherein, the hydrogen absorption pressure of the hydrogen crushing is 0.3 MPa, the dehydrogenation temperature is 560°C, the micro-grinding is carried out in an air flow mill, the grinding pressure of the air flow mill is 0.68 MPa, and the average particle size D50 of the raw alloy powder is 4 μm.
[0096] 3) The raw alloy powder is subjected to a molding process: the alloy powder obtained in step 2) is pressed and molded under magnetic field orientation with a magnetic field strength of 1.5 T to obtain a compact.
[0097] 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to finally obtain a NdFeB magnet.
[0098] The parameters of the sintering process are: sintering temperature is 1060° C., and sintering time is 8 hours.
[0099] The aging treatment process adopts a three-stage aging process: a primary aging treatment is performed after heating to 900°C at 7°C / min for 2 hours, a secondary aging treatment is performed after cooling to 200°C, a temperature is increased to 500°C at 5°C / min for 6 hours, a third aging treatment is performed after cooling to 200°C, a temperature is increased to 630°C at 5°C / min for 6 hours, and finally cooled to room temperature to obtain a final magnet.
[0100] Example 2
[0101] The same magnet formula as in Example 1 is used, and the preparation steps except for the aging treatment are the same as in Example 1.
[0102] The only difference is that the aging treatment process adopts a conventional two-stage aging process: the aging treatment includes a first-stage aging treatment and a second-stage aging treatment, the temperature of the first-stage aging treatment is 890°C, and the holding time is 4 hours; the temperature of the second-stage aging treatment is 500°C, and the holding time is 8 hours, to obtain a NdFeB magnet.
[0103] Example 3
[0104] A different magnet formula from that of Example 1 is used, and the preparation steps other than the magnet formula are the same as those of Example 1.
[0105] Magnet formula:
[0106]
[0107] Example 4
[0108] The same magnet formula as in Example 3 is used, and the preparation steps except for the aging treatment are the same as in Example 3.
[0109] The specific aging treatment method is a two-stage aging process: the aging treatment includes a first-stage aging treatment and a second-stage aging treatment. The temperature of the first-stage aging treatment is 880°C, and the insulation time is 4 hours; the temperature of the second-stage aging treatment is 550°C, and the insulation time is 8 hours to obtain a NdFeB magnet.
[0110] Example 5
[0111] A different magnet formula from that of Example 1 is used, and the preparation steps other than the magnet formula are the same as those of Example 1.
[0112] Magnet formula:
[0113]
[0114] Comparative Example 1
[0115] A different magnet formula from that of Example 1 is used, and the preparation steps other than the magnet formula are the same as those of Example 1.
[0116] Magnet formula:
[0117]
[0118] The test methods used in this application are as follows:
[0119] Microstructure test method:
[0120] Perform scanning electron microscope tests on any 10 or more cross sections of the magnet that are perpendicular to the orientation direction, and count the areas of all triangular grain boundary phases in each cross section, calculate the percentage of the area of all triangular grain boundary phases in each cross section to the total area of the cross section, and then find the average value of all cross sections as the percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section; the size of the observation area is, for example, 40μm×40μm and 75μm×75μm; the magnification is 2000 to 5000 times. According to a similar method, the percentage of the area of all R6T13M1 phases in the cross section of the NdFeB magnet to the total area of the cross section can also be obtained. Figure 1 and Figure 2 As shown, the grain boundary phase in the triangle area marked by △ is R6T 13 M1 phase, the grain boundary phase in the triangular area marked with ◇ is Fe-rich and high-M phase; the grain boundary phase in the triangular area marked with ○ is Cu-rich phase. The test results are obtained by performing composition analysis on each grain boundary phase.
[0121] The magnetic properties of the magnets were measured by a BH curve measuring instrument (NIM-200).
[0122] The magnetic properties test data of Examples 1-5 and Comparative Example 1 are as follows:
[0123]
[0124] The microstructure test results of Examples 1-5 are as follows:
[0125] Embodiment 1: NdFeB magnets include main phase grains, thin layer grain boundary phases and triangular region grain boundary phases. The thin layer grain boundary phase refers to a grain boundary phase formed between two adjacent main phase grains, while the triangular region grain boundary phase refers to a grain boundary phase surrounded by three or more main phase grains.
[0126] The area of all triangular grain boundary phases in the cross section of the NdFeB magnet accounts for 7.3% of the total area of the cross section. The triangular grain boundary phases include R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet 13 The percentage of the area of the M1 phase to the total area of the cross section is 6.25%.
[0127] The triangular grain boundary phase includes an Fe-rich high-M phase, and the ratio of Gd / R in the Fe-rich high-M phase is 5.2%.
[0128] Triangular grain boundary phase includes R6T 13 M1 phase, R6T 13 The ratio of Gd / R in the M1 phase is 7.92%.
[0129] The triangular grain boundary phase also includes a Cu-rich phase, and the ratio of Gd / R in the Cu-rich phase is 4.5%.
[0130] Embodiment 2: NdFeB magnets include main phase grains, thin layer grain boundary phases and triangular region grain boundary phases. The thin layer grain boundary phase refers to a grain boundary phase formed between two adjacent main phase grains, while the triangular region grain boundary phase refers to a grain boundary phase surrounded by three or more main phase grains.
[0131] The percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section is 6.22%, and the triangular grain boundary phases include R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.60%.
[0132] The triangular grain boundary phase includes an Fe-rich high-M phase, and the ratio of Gd / R in the Fe-rich high-M phase is 10.11%.
[0133] Embodiment 3: NdFeB magnets include main phase grains, thin layer grain boundary phases and triangular region grain boundary phases. The thin layer grain boundary phase refers to the grain boundary phase formed between two adjacent main phase grains, while the triangular region grain boundary phase refers to the grain boundary phase surrounded by three or more main phase grains.
[0134] The percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section is 7.11%, and the triangular grain boundary phases include R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet 13 The percentage of the area of the M1 phase to the total area of the cross section is 6.10%.
[0135] Triangular grain boundary phase includes R6T 13 M1 phase, R6T 13 The ratio of Gd / R in the M1 phase is 8.63%.
[0136] The triangular grain boundary phase also includes a Cu-rich phase, and the ratio of Gd / R in the Cu-rich phase is 6.21%.
[0137] The triangular grain boundary phase includes an Fe-rich high-M phase, and the ratio of Gd / R in the Fe-rich high-M phase is 8.80%.
[0138] Embodiment 4: NdFeB magnets include main phase grains, thin layer grain boundary phases and triangular region grain boundary phases. The thin layer grain boundary phase refers to a grain boundary phase formed between two adjacent main phase grains, while the triangular region grain boundary phase refers to a grain boundary phase surrounded by three or more main phase grains.
[0139] The percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section is 6.50%, and the triangular grain boundary phases include R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.64%.
[0140] Triangular grain boundary phase includes R6T 13 M1 phase, R6T 13 The ratio of Gd / R in the M1 phase is 8.81%.
[0141] Embodiment 5: NdFeB magnets include main phase grains, thin layer grain boundary phases and triangular region grain boundary phases. The thin layer grain boundary phase refers to the grain boundary phase formed between two adjacent main phase grains, while the triangular region grain boundary phase refers to the grain boundary phase surrounded by three or more main phase grains.
[0142] The percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section is 6.10%, and the triangular grain boundary phases include R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.50%.
[0143] The triangular grain boundary phase also includes a Cu-rich phase, and the ratio of Gd / R in the Cu-rich phase is 6.00%.
[0144] The triangular grain boundary phase includes an Fe-rich high-M phase, and the ratio of Gd / R in the Fe-rich high-M phase is 4.2%.
[0145] Comparative Example 1: The NdFeB magnet includes main phase grains, thin layer grain boundary phase and triangular region grain boundary phase. The thin layer grain boundary phase refers to the grain boundary phase formed between two adjacent main phase grains, and the triangular region grain boundary phase refers to the grain boundary phase surrounded by three or more main phase grains.
[0146] The percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section is 5.20%, and the triangular grain boundary phases include R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet 13 The percentage of the area of M1 phase to the total area of the cross section is 5.12%, R6T 13 The ratio R1 / R of the atomic percentage of R1 to the atomic percentage of R in the M1 phase is 9.2%.
[0147] The technical solution of the present application adds Gd or Ce to replace part of the light rare earth elements Pr and Nd; in a system with low B addition, after adding a certain amount of Gd or Ce elements, how to adjust the distribution of Gd or Ce elements in the grain boundary phase is one of the key factors of the present application. In addition, the inventors found that in the intergranular phase, Gd is more inclined to enter the triangular grain boundary phase with a higher Fe content; therefore, by adjusting the content of elements such as Cu and Ga combined with a three-stage tempering process, the technical solution of the present application can accurately control the proportion of Gd elements in the triangular grain boundary phase, reduce the Gd / R value in the Fe-rich high M phase, and reduce R6T 13 The Gd / R value in the M1 phase decreases the Gd / R value in the Cu-rich phase, thereby increasing the proportion of Pr and Nd elements in each phase. The increase in this proportion is beneficial to the demagnetization coupling effect, thereby preparing magnets with better coercive force, remanence and squareness.
[0148] Although multiple embodiments of the present application have been shown and described herein, it is obvious to those skilled in the art that such embodiments are provided only by way of example. Those skilled in the art can think of many changes, modifications and alternatives without departing from the thought and spirit of the present application. It should be understood that in the process of practicing the present application, various alternatives to the embodiments of the present application described herein can be adopted. The attached claims are intended to limit the scope of protection of the present application, and therefore cover equivalents or alternatives within the scope of these claims.
Claims
1. A neodymium iron boron magnet, characterized in that: The NdFeB magnet contains the following ingredients: R: 28~33wt% B: 0.85~0.94wt%, Co: 0.05~0.6wt%, Cu: 0.05~0.5wt%, Ga: 0.3~0.6wt%, M1: 0.05~1.1wt%, M2: 0.1~0.5wt%, Fe: 63.2~69wt%; Wherein, R is a rare earth element, R includes at least PrNd, and R includes R1; R1 is selected from one or both of Gd and Ce; M1 is at least one element selected from Al and Sn; M2 is at least one element selected from Zr, Ti and Nb; The NdFeB magnet comprises main phase grains, thin layer grain boundary phases and triangular region grain boundary phases, wherein the distribution of the triangular region grain boundary phases satisfies the following conditions: the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet accounts for 6% to 8.5% of the total area of the cross section; the triangular region grain boundary phases include R6T 13 M1 phase, M is selected from one or more of Al, Cu, Ga, Ti, Sn, Zr, Nb, T is selected from one or two of Fe and Co, and R6T 13 The ratio R1 / R of the atomic percentage of R1 to the atomic percentage of R in the M1 phase is 6.0% to 9.0%.
2. The NdFeB magnet according to claim 1, characterized in that: The content of R is 29.5 to 33 wt %, and R does not include Dy and Tb.
3. The NdFeB magnet according to claim 1 or 2, characterized in that: The composition of the NdFeB magnet includes at least one of the following features: a.Cu: 0.25-0.5wt%; b.Al: 0.5-1.1wt%; c.Ga: 0.3-0.45wt%; d.Ti: 0.15~0.3wt%.
4. The NdFeB magnet according to claim 1 or 2, characterized in that: The content of R1 is 3-7 wt%.
5. The NdFeB magnet according to claim 1 or 2, characterized in that: The distribution of the triangular region grain boundary phase meets the following conditions: the percentage of the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section is 7% to 8.5%; Preferably, the triangular region grain boundary phase includes R6T 13 M1 phase, the R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.5% to 7%, preferably 6% to 7%.
6. The NdFeB magnet according to claim 1 or 2, characterized in that: The triangular region grain boundary phase of the NdFeB magnet includes at least one of the following features: a. The triangular region grain boundary phase comprises an Fe-rich high M phase, and the ratio of the atomic percentage of R1 to the atomic percentage of R in the Fe-rich high M phase is R1 / R of 4.0% to 11.0%, preferably 4.0% to 9.0%; b. The triangular region grain boundary phase includes R6T 13 M1 phase, and R6T 13 The ratio of the atomic percentage of R1 to the atomic percentage of R in the M1 phase is R1 / R, which is 6.0% to 8.5%; c. The triangular region grain boundary phase includes a Cu-rich phase, and the ratio of the atomic percentage of R1 to the atomic percentage of R in the Cu-rich phase, R1 / R, is 4.0% to 6.5%, preferably 4.0% to 6.0%.
7. A method for preparing a neodymium iron boron magnet, characterized in that: include: 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process; 2) crushing the quick-setting alloy flakes obtained in step 1) by hydrogen, adding additives and jet milling to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 3 to 5 μm; 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.4-2.5T, to obtain a compact, or performing secondary isostatic pressing to obtain a compact; 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to finally obtain a NdFeB magnet; The aging treatment process is a three-level aging process: the temperature of the first level aging is 800-950°C, and the insulation time is 0.5-4h; the temperature of the second level aging is 450-550°C, and the insulation time is 2-10h; the temperature of the third level aging is 600-700°C, and the insulation time is 2-10h.
8. The preparation method according to claim 7, characterized in that: In the step 4), the aging treatment process further comprises: cooling to 150-250°C after the second aging, with a cooling rate of 3-8°C / min; cooling to room temperature after the third aging, with a cooling rate of 3-8°C / min.
9. The preparation method according to claim 7 or 8, characterized in that: In the step 1), the rapid solidification process includes melting the alloy raw material in a vacuum induction melting furnace at a melting temperature of 1400-1500° C., and casting the molten liquid onto a copper roller to obtain a 0.15-0.4 mm rapid solidification alloy sheet.
10. The preparation method according to claim 7 or 8, characterized in that: In the step 4), the sintering process parameters include: a sintering temperature of 1030-1120° C., and a sintering time of 4-12 hours, preferably 6-12 hours.
Citation Information
Patent Citations
R-Fe-B series sintered magnet with low B content and preparation method thereof
CN110619984A
Rare earth permanent magnet material and preparation method and application thereof
CN111243810A
R-T-B series permanent magnet material as well as preparation method and application thereof
CN111261356A
R-T-B series permanent magnet material as well as preparation method and application thereof
CN111326306A
Rare earth sintered neodymium-iron-boron magnet, preparation method thereof and application of praseodymium hydride
CN114141462A
Cited By
Sintered neodymium-iron-boron magnet and preparation method thereof
CN120824090A
Neodymium-iron-boron magnet for ultra-high-speed motor and preparation method and application thereof
CN120977712A